Mindsponge framework: Tracing students’ proactive interference - Pradina Parameswari; Ulumul Umah; Nurul Rafiqah Nasution; Susana Labuem; Analisa Fitria; Jihan Hidayah Putri (CV. FOUNDAE, 2026)
Background: Many students have difficulty distinguishing between direct and inverse proportion problems. This difficulty can cause interference during problem solving. One form of interference is proactive interference, which occurs when previously learned information disrupts the understanding of new information. In proportion problems, students’ prior knowledge of direct proportion often influences how they approach inverse proportion tasks, leading them to apply incorrect strategies. Aim: This study aims to describe the process of proactive interference experienced by students when solving proportion problems using the Mindsponge framework. Method: This study used a qualitative descriptive approach. The participants were 32 eighth-grade students from Junior High School 3 Malang. The selected subjects were students who could correctly solve direct proportion problems but applied the direct proportion concept when solving inverse proportion problems. Data were collected through proportion problem tests and interviews. Students’ written work was analyzed using indicators from the Mindsponge framework, and the findings were triangulated by comparing students’ work with interview results. Results: The results show that proactive interference occurred at three stages of the Mindsponge framework: environmental, filtering, and mindset. At the environmental stage, students made errors in observing and understanding the problem. In the filtering stage, students incorrectly determined the quantitative relationship between variables. At the mindset stage, students relied on their prior knowledge of direct proportion and frequently used the cross-multiplication strategy. Conclusion: The study indicates that proactive interference occurs when previously learned concepts dominate students’ thinking processes. The Mindsponge framework helps explain how prior knowledge influences the way students interpret and apply new information when solving proportion problems.